SISTEM INFORMASI PENILAIAN KINERJA PEGAWAI PADA LEMBAGA PEMASYARAKATAN NARKOTIKA MUARA SABAK - Akhmad Faisal Husni; Saut Siagian (Jurnal Ilmiah Matrik, 2023)
Abstract : The Class IIb Muara Sabak Penitentiary fosters and provides a Rehabilitation Program for prisoners, especially users, drug addicts in collaboration with the National Narcotics Agency (BNNP) of Jambi Province and the National Narcotics Agency of East Tanjung Jabung Regency (BNNK). Currently, the capacity is 362 inmates, which is occupied by 792 inmates, which means there is an excess of occupants. This condition causes employees to work harder. Individual employee performance is very important in achieving organizational goals. Therefore we need a performance appraisal system that is reliable and will be used as a basis for performance appraisal and organizational development, employee performance follows a goal so that each employee can assess the extent to which his performance has resulted in an expected achievement following organizational goals. This information system is built by modeling the system using UML. So that the system that was built can help the Class IIb Muara Sabak Penitentiary in determining the performance appraisal.